Introduction: maximising revenues, minimising political costs – challenges in the history of public finance of the early modern period. (10th April 2018) - 't Hart, Marjolein; Brandon, Pepijn; Sánchez, Rafael Torres
Abstract : Taxation is accepted as a fact of modern life, despite recurring political conflict over the nature and direction of fiscal policies. Most financiers regard obligations issued by the state as a safe investment option. Neither taxation nor state obligations were taken for granted during much of the history of public finance, however, at least not before the early 1800s. The 'tax state' developed in fits and starts, driven by the exigencies of warfare, which provided the main rationale for raising state income. Although wartime fiscal innovations eventually facilitated the rise of an efficient military state, the options available for implementing such improvements and preferences for specific fiscal or financial instruments varied greatly across early modern states. Focusing on the 'long' eighteenth century, this introduction presents a framework for assessing these differences and introduces the other articles in this special issue.